Analisis Tingkat Kepuasan Penumpang Terhadap Jasa Pelayanan Penyeberangan Menggunakan Metode Logika Fuzzy Servqual Pada PT. ASDP Indonesia Ferry Cabang Sibolga - Rini Simanullang; Murni Marbun (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2021)
Service can be said to be good, if the service can meet passenger satisfaction, satisfaction is achieved if the service received by passengers can exceed what is expected. In Fuzzy Logic, decision making is done by using an inference system called the fuzzy inference system which is a process of making conclusions based on Fuzzy Logic reasoning. Among the various models for measuring service quality (servqual), servqual is the most widely used method because of its high frequency of use. The criteria for measuring passenger satisfaction are physical form, reliability, response, empathy, assurance. From the calculation of the Servqual value (gap) per dimension, the first rank is the Reliability dimension of 7.65, as is the case with the calculation per criterion where the three priority criteria are part of the Reliability dimension. For the second order, Tangibles is 0.17, the third order is the Assurance dimension -0.05, the fourth order is empathy at 0.20, and the last or fifth order is Responsiveness of -11.48. This system is designed to analyze the level of passenger satisfaction at PT. ASDP Sibolga Branch using the PHP programming language. Data management using the MySQL database.